2019
DOI: 10.4084/mjhid.2019.015
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Immunohistochemical P53 Expression in Bone Marrow Biopsy in Higher Risk Mds: A Pilot Study

Abstract: Background and objectives: Mutations of the TP53 gene have an unfavorable prognosis in Myelodysplastic Syndromes (MDS). The product of the TP53gene is the p53 protein. Most of TP53mutations entail the accumulation of the protein in the nucleus of tumor cells. The immunohistochemical (IHC) staining for p53 can be a surrogate suggesting a mutational status and, if overexpressed, seems to be of prognostic value by itself. The best prognostic cut-off value of overexpression is controversial. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…MYC expression did not show any prognostic impact on OS in MDS patients (Figure 1F). In contrast, MDS patients with p53 expression showed significantly poor OS compared to MDS patients without p53 expression ( P < .0001; Figure 1G), compatible with findings in the literature 12,14,16 …”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…MYC expression did not show any prognostic impact on OS in MDS patients (Figure 1F). In contrast, MDS patients with p53 expression showed significantly poor OS compared to MDS patients without p53 expression ( P < .0001; Figure 1G), compatible with findings in the literature 12,14,16 …”
Section: Resultssupporting
confidence: 90%
“…Expression of p53 is significantly increased in both AML and MDS patients compared with the control group in our study. Similar to previous reports, 10,12,14,15,17,18 our study also found that p53 expression is a poor prognostic factor and confers a negative impact on OS in AML and MDS patients. P53 expression is correlated with TP53 aberration in 23 AML patients (85%, n = 27) and seven MDS patients (78%, n = 9), respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations